Post-thaw dimethyl sulfoxide reduction in autologous peripheral blood progenitor cell suspensions - Miroslava Jandová; Pavel Měřička; Jiří Gregor; Miriam Lánská; Aleš Bezrouk; Dana Čížková; Jakub Radocha (Hematology, Transfusion and Cell Therapy)
Background and objectives: Dimethyl sulfoxide has become the most common cryoprotectant used for cryopreservation of hematopoietic progenitor cells because of its efficiency, regardless of its potentially toxic side effects. Its application is considered safe, provided that the daily dose administered does not exceed 1 gram per kilogram of patient weight. Indications for its reduction after thawing are limited to patients with high risk of malignant arrhythmia and those with severely impaired renal function. However, dimethyl sulfoxide reduction can lead to the loss of viable progenitors. Methods: A retrospective study of viable hematopoietic progenitor cell recovery after dimethyl sulfoxide reduction was performed with 13 patients (nine men, four women) with secondary amyloidosis in multiple myeloma (n = 9), primary amyloid light chain amyloidosis (n = 3), or severe adverse reaction at the beginning of the hematopoietic progenitor cell concentrate infusion (n = 1). The Wilcoxon signed-rank test was used. Results: The results of the dimethyl sulfoxide reduction process showed a high recovery of viable nucleated cells (median: 120.85 %), and of viable mononuclear cells (median: 104.53 %). There was a significant decrease in total number of viable CD34+ cells in comparison with data obtained after original collection (median: 51.49 %). No significant decrease in colony-forming unit capacity was observed after dimethyl sulfoxide reduction (median: 93.37 %). Conclusion: The dimethyl sulfoxide removal process and total process recoveries revealed considerable individual variability. To minimize the risk of prolonged engraftment or non-engraftment, it is important to apply this process only to high-risk patients.